All our fears: gender-based violence and terror in The things we lost in the fire, by Mariana Enríquez - Olmedo, Nadina (2022)
Las cosas que perdimos en el fuego (2016), by Mariana Enríquez, deals with terror and the strange in shocking stories that, although framed within “realism”, speak of fear and violence established from everyday life from some unfolding or disturbance of reality, which in most cases involves female characters, girls, boys and adolescents.The different stories are presented as a catalog of all our fears as a society: the scourge of drugs and unplanned motherhood, the objectified female body, and even the empowerment of women in such circumstances. Through disturbing and ominous environments, the author builds a terror from everyday life, which represents, denounces and even resists violence against women.In my analysis, I will try to dismantle the representation of gender and childhood issues and the construction of a “social terror” -following Elsa Drucaroff- in three of the stories in this collection mainly around the persistence of social mandates, but also to the resistance to them, to the need to “burn them” as the title of the book under discussion indicates.